Ocena pogostosti kroničnih bolezni med polnoletnimi prebivalci Slovenije - Softič, Nina (Zdravstveno varstvo, 2011)
Background: This study is part of the research entitled Self-medication amongSlovene citizens . The aim of this paper is to show the prevalence of chronic diseases in Slovenia and to identify the characteristics of people with chronic health problems. The main emphasis is placed on the prevalence ofchronic diseases in general population by age and educational and employmentstatus. Methods: A cross-sectional study, based on an anonymous questionnaire, was mailed to one thousand randomly chosen inhabitants in all regions of the Republic of Slovenia. The data were processed statistically using the chisquare test and t-test, depending on the nature of the variable and multivariable analysis. Results: Forty-one percent of all questionnaires were analysed. Health problems in the previous year were reported by 70.5 % ofrespondents. Individuals suffering from chronic diseases were on average 15 years older than those reporting no chronic health problems. Patients with diabetes had the highest mean age (667 + 11.4), there followed those with cancer (65.1 + 18.7) and those with rheumatic disease (64.5 + 14.6). The prevalence of all chronic diseases was highest in individuals with lower education and in pensioners. Conclusions: The study has shown a high prevalence of chronic diseases in Slovenia. It is significantly higher in the population with lower socio-economic and employment status. More attention should therefore be paid to diagnosing and preventing chronic diseases, in these groups.
Keywords: družinska medicina; izobrazba; kronične bolezni; starost; zaposlitev